2019
DOI: 10.1186/s13063-019-3609-8
|View full text |Cite
|
Sign up to set email alerts
|

Covered stents versus Bare-metal stents in chronic atherosclerotic Gastrointestinal Ischemia (CoBaGI): study protocol for a randomized controlled trial

Abstract: Background Chronic mesenteric ischemia (CMI) is the result of insufficient blood supply to the gastrointestinal tract and is caused by atherosclerotic stenosis of one or more mesenteric arteries in > 90% of cases. Revascularization therapy is indicated in patients with a diagnosis of atherosclerotic CMI to relieve symptoms and to prevent acute-on-chronic mesenteric ischemia, which is associated with high morbidity and mortality. Endovascular therapy has rapidly evolved and has replaced surgery as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 30 publications
0
11
0
3
Order By: Relevance
“…The results of a randomised controlled trial (NCT02428582) comparing the CS and BMS are awaited. 107 Comparative data on PMAS with a drugeluting stent (DES) is not available in the literature.…”
Section: D 96%mentioning
confidence: 99%
See 1 more Smart Citation
“…The results of a randomised controlled trial (NCT02428582) comparing the CS and BMS are awaited. 107 Comparative data on PMAS with a drugeluting stent (DES) is not available in the literature.…”
Section: D 96%mentioning
confidence: 99%
“…A randomised controlled trial comparing the BMS and CS is currently underway and results are expected in 2021. 107 However, questions concerning the role of the DES in the mesenteric arteries and the optimal revascularization strategy in patients with an in-stent stenosis remain unanswered. Development of validated software tools for accurate grading of in-stent stenosis on CTA, using the transstenotic mean arterial pressure gradient under angiography as a reference, is another important research topic.…”
Section: D 83%mentioning
confidence: 99%
“…Similarly, they reported that the freedom from restenosis (89 6 10% vs 49 6 14%; P < .04), freedom from symptom recurrence (100% vs 64 6 9%; P ¼ .001), and freedom from reintervention (100% vs 72 6 9%; P ¼ .03) were all better for the covered stents in the reintervention group. Notably, van Dijk et al 130 have published the study protocol for a randomized trial (CoBaGI) comparing balloonexpandable covered vs balloon-expandable bare-metal stents for CMI.…”
Section: Detailed Justificationmentioning
confidence: 99%
“…Technical success was achieved in 89.5% of 38 revascularizations. Stent specifications could not be assessed because 19 of the 38 (50%) revascularization procedures were included in an ongoing double blinded randomized controlled trial, comparing the patency of bare metal stents (Palmaz Blue; Cordis, Baar, Switzerland) with the patency of covered stents (V12, Atrium Medical Corporation, Merrimack, NH) (13).…”
Section: Variablesmentioning
confidence: 99%